ANALISIS METODE TREND MOMENT DALAM FORECASTING UNTUK MEMPREDIKSI JUMLAH PENJUALAN PADA RESTORAN AYAM GEPREK GOKIL - Rizky Prayoga; Anita Anita; Josua Silaban; Saut Parsaoran Tamba (Politeknik Bisnis Indonesia, 2023)
Predictions are things that might be done so that actions taken in the future are more effective and efficient. Predictions in sales are absolutely necessary so that companies / institutions can avoid big losses. Gokil Chicken Resto is a company engaged in the culinary field. Even though it is a Resto brand, it must have a business license in the form of a CV so that it can be said to be a company. The Gokil Chicken Resto has a problem, namely in the loss of procuring raw materials to be produced in a culinary menu called Gokil Geprek Chicken. In a condition, sometimes the procurement of these materials will be left quite a lot or even run out. This causes losses in terms of cost and also consumer disappointment as well. For this reason, research is needed in the form of sales predictions so that it can help minimize losses by procuring materials that are more effective and efficient. This study uses the trend moment method in analyzing sales to produce predictive numbers. The method of precise prediction accuracy uses MAPE (Mean Absolute Percentage Error). The accuracy of the prediction accuracy obtained is 99.36%.